KEBERADAAN NEMATODA ENTOMOPATOGEN (NEP) PADA PERTANAMAN HORTIKULTURA DI LAHAN GAMBUT DENGAN FREKUENSI APLIKASI PESTISIDA YANG BERBEDA - Kurnia Sari (Fakultas Pertanian Universitas Tanjungpura, 2019)
Entomopathogenic nematodes are types of biological agents that live on the ground. The population can decrease exposure to chemicals in the form of pesticides that are too frequent. This study aims to determine the population density of EPN on peat land used for horticultural agriculture with the intensity of application of low, medium, and high pesticides (PI). The design of this study uses a Completely Randomized Design (CRD) with 3 preparations, and 15 replications, so that 45 samples will be obtained. Research parameters regarding bait insect mortality, population of NEP / ml, collection of NEP morphology, biochemical collection of bacterial symbionts, and soil analysis. The results showed that the highest PI was 51.7%, the lowest NEP density was 551 JI / ml and the lowest NEP diversity was only Steinernema carpocapsae. While on medium PI land and low PI land. mortality larvae reached 80.67 % and 78.7 %, and populations of 1.112 JI /ml and 752 JI / ml. The highest diversity was found in the medium PI land with two types of NEP, namely Steinernema carpocapsae and Heterorhabditis bacteriophora. While the abundance of the population of Steinernema carpocapsae is on low PI land.